Cell-ECM traction force modulates endogenous tension at cell-cell contacts - Maruthamuthu, Venkat; Sabass, Benedikt; Schwarz, Ulrich S. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Cells in tissues are mechanically coupled both to the ECM and neighboring cells, but the coordination and interdependency of forces sustained at cell-ECM and cell-cell adhesions are unknown. In this paper, we demonstrate that the endogenous force sustained at the cell-cell contact between a pair of epithelial cells is approximately 100 nN, directed perpendicular to the cell-cell interface and concentrated at the contact edges. This force is stably maintained over time despite significant fluctuations in cell-cell contact length and cell morphology. A direct relationship between the total cellular traction force on the ECM and the endogenous cell-cell force exists, indicating that the cell-cell tension is a constant fraction of the cell-ECM traction. Thus, modulation of ECM properties that impact cell-ECM traction alters cell-cell tension. Finally, we show in a minimal model of a tissue that all cells experience similar forces from the surrounding microenvironment, despite differences in the extent of cell-ECM and cell-cell adhesion. This interdependence of cell-cell and cell-ECM forces has significant implications for the maintenance of the mechanical integrity of tissues, mechanotransduction, and tumor mechanobiology.